'...como se fosse lógico': considerações críticas da medicalização do corpo infantil pelo TDAH na perspectiva da sociedade normalizada - Moraes, Rodrigo Bombonati de Souza (2012)
This research shows us that we are living in the era of medicalization, of the disorders, and pathologies (CONRAD, 1992; ROSE, 2001; VICENTIN, 2010). In the last decade the number of mental diseases diagnosed, specifically in children, who we consider normal from Canguilhem’s (2010) perspective, but the medical-scientific eye consider mental disorder has grown. This way discourses or mechanisms, which allows the psychiatric community to change different behaviors in pathology in a way that they can act on the bodies authoritatively. Amongst them is the Attention Deficit Hyperactivity Disorder (ADHD), analyzed as an empirical object of this research, which is a broader discursive field identified as medicalization (CONRAD, 1992; ROSE, 2001; FOUCAULT, 1988; ILLICH, 1975), composed of various institutions such as: psychiatry, pharmaceutical companies, schools, families, justice system, associations of people with the disorder, and non-specialized media. This happens when there is an analytic displacement of a socio-cultural behavior into a medical field to be diagnosed and then treated as if it was pathologic. To collect information about ADHD, we examined the discourse of five psychiatrists, gathered thought previously given interviews, 114 reports from the newspaper ‘Folha de São Paulo’, published during the period between 1997 and 2011, the site of the Association of Attention Deficit (ABDA) and some of its productions (meetings, informative materials and texts of its members), and finally, the Bills (PL's) in progress in the legislative house in the city, the state of Sao Paulo and the Brazilian Federation. Making use of important concepts which we considered relevant to the Genealogy of Power and the Archaeology of Knowledge (FOUCAULT, 2007, VEYNE 2011), and the Theory of Discourse (HOWARTH, 2000), we are seeking to understand how the medicalizalization discourse produce effects on the bodies, transforming the lack of attention and the over activity present in a child in a mental disorder. We noticed that it is done, amongst other reasons, to enhance or to improve the performance of individuals, a demand made not only by the schools, but by the economy of our society. This demand appears to be identified in society as normalized (FOUCAULT, 2006), in risk (BAUMAN, 2008; BECK, 2010), or controlled (DELEUZE, 1992), where to avoid possible harm to the individual and to society, the bodies must to be kept under control. That is why science, based in knowledge of genetics and neurology, dissects the body in illnesses, establishing a new form of subjection (DELEUZE; GUATTARI, 1996), the abnormal. The abnormality appears at the border between the expected behavior and deviating, to the extent that the latter appears as embarrassment to sociability, and especially to productivity. To normalize would then be not only a function of the disciplinary power, it would be also part of the biopower, the power over life (FOUCAULT, 1988) which acts over the bodies and the population, respectively, synthesized in this research critically named as medication. Moreover, when we opened this field of discourse, we realized that although there is resistance, the medicalization of children due to ADHD in Brazil has succeeded in its ambitions, and in the promulgation of laws and the proper identification of the disorder by common sense, the ultimate boundaries of power over the bodies.